Medullary carcinoma and carcinoma of Synchronous thyroid Hürthle cells: a rare injury association Presentation of a clinical case and review of the bibliography - Cimarra, Luis; Gutiérrez, Fernando; Acevedo, Carlos; Rosasco, Mariana; Mariño, Ana (Cirugía del Uruguay, 2000)
The authors present a rare case of synchronic and independent lesiona! association of medular carcinoma of the thyroid with nade methastasis and Hürthle ce// carcinoma of the contralateral thyroid /obe. There is a lack of similar references in the reviewed literature. The authors describe in detail diagnostic and therapeu- tical steps followed with this patient. Bibliography revision made possible an update of diagnostic, therapeutical and prognostic aspects of both types of thyroid cancer. The patient is disease free and in good condition ten months after surgery, with a strict follow-up.